Non-destructive measurement of current distribution in HTS conductors - Johnston, MD; Everett, J; Dhalle, M; Caplin, A; Moore, J; Fox, S; Grovenor, C; Grasso, G; Hensel, B; Flukiger, R (1996)
We describe scanning Hall probe studies of the current distribution in BSCCO 2223, 2212 and TSCCO 1223 conductors, by measurement of the self-field and remanent flux profiles. The pattern of current flow is dependent on the total current amplitude as well as the underlying microstructural features. We correlate these local studies with macroscopic information from transport and magnetisation experiments, and make comparison between the three materials systems. BSCCO 2223 is found to be dominated by the microstructural inhomogeneities whereas the properties of BSCCO 2212 and TSCCO 1223 are governed by the intrinsic electrodynamics.